European Organisation for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group Experience with Advanced/Metastatic Epithelioid Sarcoma Patients Treated in Prospective Trials: Clinical Profile and Response to Systemic Therapy. Issue 7 (July 2018) - Touati, N.; Schöffski, P.; Litière, S.; Judson, I.; Sleijfer, S.; van der Graaf, W.T.; Italiano, A.; Isambert, N.; Gil, T.; Blay, J.Y.; Stark, D.; Brodowicz, T.; et al.
Abstract: Aims: Epithelioid sarcoma is a soft tissue sarcoma associated with a high rate of local recurrence after wide resection and high incidence of distant metastasis. Little is known about the clinical course and response to systemic treatments in epithelioid sarcoma patients. We carried out a retrospective analysis of clinical data from epithelioid sarcoma patients to provide a reference for the design of future epithelioid sarcoma-specific studies. Patients and methods: Data from patients with epithelioid sarcoma entered in prospective multi-sarcoma phase II/III trials were pooled: EORTC trial 62012 (doxorubicin versus doxorubicin/ifosfamide), 62043 (pazopanib), 62072 (pazopanib versus placebo) and 62091 (doxorubicin versus trabectedin). Patients had either a local or a centrally confirmed diagnosis of epithelioid sarcoma, had inoperable/metastatic disease at study entry and were eligible for the according trial. Response was assessed according to RECIST 1.1. Progression-free survival (PFS) and overall survival were calculated from date of entry. Results: Among 976 patients with advanced sarcomas, 27 epithelioid sarcoma patients (2.8%) were eligible for the analysis (17 men, median age at diagnosis 50 years, range 19–72). Eighteen (66.7%) received chemotherapy as first-line treatment (five doxorubicin, eight doxorubicin/ifosfamide, two pazopanib, three trabectedin) and nine (33.3%) received pazopanib as second line or later. The primary tumour was located in the lower extremity ( n = 8; 29.6%), upper extremity ( n = 5; 18.5%), retro/intra-abdominal ( n = 4; 14.8%) and in other locations ( n = 10; 37.0%). At entry, metastases were mainly found in lung ( n = 17; 63%), lymph nodes ( n = 9; 33.3%), bone ( n = 8; 29.6%) and soft tissue ( n = 7; 25.9%). The best response for first-line patients was four partial responses (22.2%), 10 stable disease (55.6%) and four progressive disease (22.2%). In subsequent lines, pazopanib achieved one partial response (11.1%), four stable disease (44.4%) and four progressive disease (44.4%). All patients but one progressed on treatment. The median PFS and overall survival were 3.8 (95% confidence interval 2.2–4.8) and 10.8 months (95% confidence interval 8.1–21.3), respectively. Five patients were still alive at the time of the according trial analysis. Conclusion: With all limitations of such a rare disease and small data set, objective response and survival outcomes are similar in epithelioid sarcoma to non-selected sarcoma populations. The clinical testing of novel systemic treatments for epithelioid sarcoma remains an unmet medical need and a high priority. Highlights: Epithelioid sarcoma is a rare disease representing only 2.8% of patients treated with systemic therapy into EORTC trials. Objective response and survival outcomes are similar in epithelioid sarcoma to non-selected sarcoma populations. This study reinforces the existing knowledge on systemic therapy in this rare type of sarcoma, notably with pazopanib. The clinical testing of novel systemic treatments for epithelioid sarcoma remains an unmet medical need and a high priority.